The Association of Stimulation and Food Intake with Motor Development among Toddlers in Puskesmas Belimbing - Azrimaidaliza, Azrimaidaliza; Destine, Reviona; Helmizar (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Background: Children's brain development up to 3 years old reaches 80%. At this age, delays in motor development can be detected so that further intervention can be carried out. Objectives: To determine the factors which have an association with motor development among toddlers. Methods: A cross-sectional research design was undertaken in which the sample was a 78 of mothers of toddlers 6-36 months in Puskesmas Belimbing. The sample was chosen by proportional random sampling technique. Data analysis was carried out in the form of univariate, bivariate and multivariate with the IBM SPSS Statistics for Windows Software. Results: This research found the majority of toddlers' fine motor (80.8%) and gross motor development (84.6%) were in the normal category. The bivariate analysis results indicated an association between iron intake and the fine motor (p value=0.008) and gross motor development (p value =0.045). There was an association between stimulation and fine motor (p value =0.001) and gross motor development (p value =0.009), as well as nutritional status according to weight-for-height which had an association with the fine motor (p value =0.034) and gross motor development (p value =0.047). Meanwhile, nutritional status according to height-for-age had only an association with fine motor development (p value =0.016). The factor most related to fine and gross motor development was stimulation (p value = 0.006; OR=6.559; 95%CI=1.704-25.249 and p value=0.007; OR=6.333; 95%CI=1.671-23.999). Conclusion: It was discovered that the factor most related to fine and gross motor development in toddlers aged 6-36 months was stimulation provided by parents.